Hydrologic behaviour of residual soil slopes in Singapore - Rahardjo, Harianto (2011)
Monitoring hydrologic responses of slopes is critical for advancing hillslope hydrologic studies. Storm- and time-based continuous hydrologic responses from three instrumented hillslopes in Singapore were monitored for a period of 420 days to observe the impact of rainfall on the pore-water pressure changes and runoff generation. Analyses of the hydrologic data indicate that only about 37% of the annual rainfall events are capable of producing runoff, and a threshold rainfall of about 10 mm is required to produce runoff. The seasonal distribution of pore-water pressures showed that the slopes experience high matric suctions during dry periods that are comparable to matric suctions observed in other tropical climates, and positive pore-water pressures during wet periods, that are higher than in other geographic locations. A high correlation between the increase in pore-water pressure and the daily rainfall may provide a convenient estimate of the increase in pore-water pressure due to the daily rainfall. The variability of hillslope hydrologic responses from storm to storm is distinctive when compared with previous results at other geographic locations.